JPE Turnaround Times (Journal of Political Economy, 2022)
Previous articleNext article FreeJPE Turnaround TimesPDFPDF PLUSFull Text Add to favoritesDownload CitationTrack CitationsPermissionsReprints Share onFacebookTwitterLinked InRedditEmailQR Code SectionsMoreSummary Statistics of Turnaround Times, Current JPE Editors Outcome of 1st Round DecisionsDays to Decision MeanMedianDesk Rejection55%76Reject with Reviews40%9282Revise5%125111View Table Image Previous articleNext article DetailsFiguresReferencesCited by Journal of Political Economy Volume 130, Number 11November 2022 Article DOIhttps://doi.org/10.1086/722926 Views: 664Total views on this site © 2022 The University of Chicago. All rights reserved.PDF download Crossref reports no articles citing this article.